Analisis Mutu Layanan Kesehatan Tradisional di Puskesmas Kota Palembang Tahun 2024 - Evayanti; Wahyudi, Arie; Harokan, Ali (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2024)
Health developmentis part of national development aimed at increasing awareness, willingness and ability to live healthily for everyone in order to achieve the highest level of public health. Efforts to realize this level of health can be in the form of traditional health services (Traditional Health). The aim of this researchis to look at the factors related to the quality of traditional health services at the Palembang City Health Center in 2024. The method in this research is a quantitative method with a cross-sectional approach. The research was conducted at the Palembang City Health Center with a population of 41 and the sampling technique was total sampling. Statistical tests use the Chi Square test. Multivariate analysis in this study used multiple logistic regression analysis. The research results showed that there was a relationship between age (p value=1.000), education (p-value=0.518), employment status (p-value=0.144) and length of service (p-value=0.588), a relationship between technical competency (p-value=0.015), service effectiveness (p-value=0.002), Service comfort (p-value=0.012) Service security (p-value=0.020) Human relations (p-value=0.001), Service continuity (p-value=0.000), Service time (p-value=0.012) with the quality of traditional health services at the Palembang City Health Center in 2024. The continuity of service variable is the most dominant variable because the p-value is 0.003 (<0.05) with OR=30,891. It was concluded that there is no relationship between age, education, employment status and length of work with the quality of traditional health services at the Palembang City Health Center in 2024. There is a relationship between technical competency, service effectiveness, service comfort, service security, human relations, continuity of service, service time and the quality of health services traditional services at the Palembang City Health Center in 2024. The continuity of service variable is the most dominant variable.